Relationship between Knowledge Sharing, Absorptive Capacity, and Innovation Capability: Empirical studies in minimarkets - Sri Raharso - (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to identify the relationship between knowledge sharing, innovation capabilities, and absorptive capacity. The study was conducted on 209 employees of a minimarket, in Bandung, West Java. Sampling was done incidentally. Factor analysis produces five factors for which construct validity is acceptable. Empirically, the multiple regression results support the research hypothesis. Knowledge sharing positively and significantly affects innovation capability and absorptive capacity. Furthermore, absorptive capacity partially mediates the relationship between knowledge sharing and innovation capabilities.